Improving the cosmetic outcome of Salter osteotomy through the modification of iliac crest graft harvesting site: a pilot clinical study. Issue 6 (6th November 2022) - Yeganeh, Ali; Moghtadaei, Mehdi; Farahini, Hossein; Amiri, Shayan; Mahmoudi, Mani; Hamidpour, Yasaman; Hajializade, Mikaiel
Abstract : Background: The conventional graft harvesting site in a Salter osteotomy might impair the cosmetic appearance of patients with developmental dysplasia of the hip (DDH). The authors evaluated if an alternative graft donor site on the iliac bone could eliminate this concern. Methods: In a prospective study, 23 patients who had DDH with an indication for Salter osteotomy were included. In 10 patients (study group), the vertical triangular graft was harvested from the one-third anterolateral section of the iliac wing. In the remaining 13 patients (control group), the graft was harvested from the conventional site. The radiographic measures, including acetabular index and center edge angle, Severin criteria, clinical outcomes (McKay criteria), and complication rates of the two groups were compared. Results: The clinical outcome, acetabular index, center-edge angle, and Severin criteria of the patients of the two groups were statistically comparable. Union of harvested sites was seen in all patients. The mean duration of surgery and blood loss were statistically comparable ( P =0.49 and P =0.33, respectively). The rate of osteonecrosis was similar in the two groups. The only graft site morbidity was the anterior superior iliac spine (ASIS) asymmetry that was seen in all patients of the control group and no patients of the study group; a mean horizontal level difference of 2.2±0.5 cm was observed between the affected and unaffected ASIS of the control group. Conclusions: Vertical triangular graft harvest from the one-third anterolateral section of iliac wing in Salter osteotomy improves the cosmetic outcome through the reduction of pelvic deformity. Level of Evidence: Level III.